Ninja assassin - Bradford, Chris (Edinburgh: Barrington Stoke, 2014)
"When Taka's mother is killed in battle, Taka vows to seek justice. He enlists his friends Cho and Renzo and, armed by the Grandmaster, the three set out to confront Akemi's killer. But they all know this could be a one-way mission"-
Keywords: Adventure stories